Analyzing Difficulties in Speaking Arabic and Their Solutions Based on the Book Standards of Arabic Language Skills for Non-Native Speakers - Muhammad Feri Basrianto (Publikasi Indonesia, 2025)
This article aims to analyze the difficulties students face in speaking Arabic from the perspective of the book Standards of Arabic Language Skills for Non-Native Speakers and offer practical solutions that can be used as a reference to address these difficulties, both for students learning Arabic and for educators in designing teaching method. This research uses a library research method, involving examining and analyzing data related to and relevant to this study. In this study, data collection is conducted through document analysis, specifically the book Standards of Arabic Language Skills for Non-Native Speakers. The researcher will describe the data found in the book in detail, identify the difficulties faced by students in speaking Arabic, and provide relevant solutions. From the analysis, the researcher found nine fundamental factors that cause difficulties in speaking Arabic, which are the lack of practice in speaking Arabic, constructing sentences and understanding them, limited vocabulary, abbreviation and omission, dialect differences, idioms, lack of understanding of grammar, eloquence (balaghah), and the conversation partner. The solutions offered by the researcher to overcome these problems are The Power of Two method, the WhatsApp application, Quizlet and Wordwall, the drill method, the use of social media, CALL and websites, the Korsul Ajib media, the Lectora Inspire application, and the HelloTalk application.